2005
DOI: 10.1021/jm0401560
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Mimetic Peptide Inhibitors of Angiogenesis and Tumor Growth:  Design, Synthesis, and Optimization of Pharmacokinetics and Biological Activities

Abstract: The heptapeptide 1, NAc-Gly-Val-DIle-Thr-Arg-Ile-ArgNHEt, a structurally modified fragment derived from the second type-1 repeat of thrombospondin-1 (TSP-1), is known to possess antiangiogenic activity. However, therapeutic utility could not be demonstrated because this peptide has a very short half-life in rodents. To optimize the PD/PK profile of 1, we initiated a systematic SAR study. The initial structural modifications were performed at positions 5 and 7 of peptide 1 and at the N- and C-termini. Out of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 20 publications
2
132
1
Order By: Relevance
“…Clinically, one TSP-1 mimetic-ABT-510-has been developed that is currently in clinical trials for several solid organ malignancies (Haviv et al 2005). To date, data from phase I trials have shown a favorable toxicity profile, as well as linear and time-independent pharmacokinetics, and biologically relevant plasma concentrations, in patients with various solid organ malignancies (Hoekstra et al 2005(Hoekstra et al , 2006Gordon et al 2008;Nabors et al 2010).…”
Section: Exogenous Thrombospondins and Their Derivativesmentioning
confidence: 99%
“…Clinically, one TSP-1 mimetic-ABT-510-has been developed that is currently in clinical trials for several solid organ malignancies (Haviv et al 2005). To date, data from phase I trials have shown a favorable toxicity profile, as well as linear and time-independent pharmacokinetics, and biologically relevant plasma concentrations, in patients with various solid organ malignancies (Hoekstra et al 2005(Hoekstra et al , 2006Gordon et al 2008;Nabors et al 2010).…”
Section: Exogenous Thrombospondins and Their Derivativesmentioning
confidence: 99%
“…Although the mechanisms by which these materials support and promote a constructive remodeling process are only partially understood, it appears clear that rapid degradation of the scaffold material with concurrent release of both intact growth factors and newly generated bioactive matricryptic peptides as well as the provision of unique surface architectures are factors that play an important role. [34][35][36][37][38][39][40][41] The ability to promote constructive remodeling in vivo has also been shown to be highly dependent on the methods used in preparing the scaffold material. 19,20,42 For example, chemical crosslinking is often used to increase the mechanical strength of a scaffold material, to slow degradation, or to mask cellular epitope that may remain within the scaffold material after decellularization.…”
Section: Figmentioning
confidence: 99%
“…One way of reducing these manufacturing costs may be to identify component peptides from within these molecules that retain antiangiogenic activity. For example, a modified nonapeptide, ABT-510, derived from the second type-1 repeat of TSP-1 has shown promising preclinical and clinical antiangiogenic activity (Haviv et al, 2005).…”
Section: Peptide Fragmentsmentioning
confidence: 99%